Managing the Environment, Managing Ourselves : a History of American Environmental Policy - Andrews, Richard N. L. (Yale University Press, 2020)
In the third edition of this definitive book, Richard N.L. Andrews looks back at four centuries of American environmental policy, showing how these policies affect contemporary environmental issues and public policy decisions, and identifying key policy challenges for the future. Andrews crafts a detailed and contextualized narrative of the historical development of American environmental policies and institutions. This volume presents an extensively revised text, with increased detail on the fifty-year history of the modern environmental policy era and is updated through the Obama and Trump administrations.